Design and fabricate storage cabinet for turret punch tool - Muhammad Afiq, Ahmad Mustaza (2008)
Designing and fabricating a storage cabinet is a product fulfills customer needs. This project is mostly related to storage cabinet and turret punch tool. This project uses many materials such as zinc, hollow steel bar, galvanized iron and other. This project involves with some mechanical process in the fabrication and assembling procedure such welding, bending, shearing and etc. Overall, this project involves with many processes, starting from the designing concept, fabrication and assembling. Even though there are many types of cabinet in the market, the completion of this new model provides a more practical usage.